Association between timing of exanthema subitum and febrile seizures: The Japan environment and children’s study - Hisao Okabe; Koichi Hashimoto; Mika Yamada; Takashi Ono; Kazufumi Yaginuma; Yohei Kume; Mina Chishiki; Akiko Sato; Yuka Ogata; Karin Imaizumi; Tsuyoshi Murata; Hyo Kyozuka; et al. (PLoS ONE, 2025)
Recently, episodes of exanthema subitum (ES) have been occurring later than expected in Japanese patients, though the effects of this delayed timing remain unclear. Therefore, this study examined the association between ES timing and febrile seizure (FS) in Japanese children. Information on the diagnoses of ES and FS was obtained from the Japan Environment and Children’s Study, a nationwide prospective birth cohort study including 97,410 mothers and their children. Two groups were created: early ES (first ES episode between birth and 11 months of age) and late ES (first ES episode between 12 and 23 months of age) groups. Multivariate logistic regression analyses were performed to compare the cumulative incidence rate of FS between the groups. Moreover, because a single episode of fever implies that the ES and FS occurred simultaneously, we examined the association between the ES timing and the simultaneous co-occurrence of FS with ES in a limited cohort with one fever episode until the age of 24 months. In total, 27,238 full-term children were included, with 12,565 (46.1%) in the early ES group and 14,673 (53.9%) in the late ES group. Late ES was estimated to increase the cumulative incidence risk of FS until the age of 24 months (adjusted odds ratio 1.46; 95% confidence interval [1.32–1.61]) and 48 months (1.26 [1.15–1.37]). The limited cohort included 1,022 children, and late ES was estimated to increase the risk of FS with ES (4.39 [1.48–13.02]). Late ES is estimated to increase the risk of FS. Further basic research and cohort studies, including virological examinations, are required to elucidate the pathogenesis of ES with FS.